Muslim Rimba: Dialectic of Indigenous Belief Bukit Dua Belas National Park (TNBD) Jambi - Ramli, Supian; Muspawi, Mohammad; Rahman, K.A.; Sobri, Muhammad; Rafi’i, Muhammad (MKWK PAI Universitas Jambi, 2023)
Islam is the universal belief of mankind and as a dialogical religion is able to interact with various beliefs, various cultures and local traditions that develop in a multicultural society such as Indonesia.